Characteristics and Growth of Microbial Consortiumi in Media Containing Eearth Oil - Samer Ali (International Journal of Science and Society, 2020)
Laboratory microcosm observation were conducted to study the effect of media culture containing oil spill in microbial growth ability . Laboratory microcosms was inoculated with oil microbial consortia isolated from oil spill sample in Cepu oil field. Based on the colony characteristic differentiation, 5 microbial types identified from the sample. At the end of enrichment period and acclimatization on the BH media containing 5% Cepu crude oil, all isolates as microbial consortia put into growth experiment media. The experiment proved that microbes could be able utilizing oil as carbon source for their cell multiplication. The results showed the more the turbidity concentration increase, the more the microbial population rise. These studies indicates that reducing oil spill utilizing in situ bioremediation technologies can be realized.